Potential of the Middle Cambrian Aquifer for Carbon Dioxide Storage in the Baltic States - Jānis Krūmiņš; Māris Kļaviņš; Aija Dēliņa; Raivo Damkevics; Valdis Segliņš (Energies, 2021)
The importance of CO2 removal from the atmosphere has long been an essential topic due to climate change. In this paper, the authors aim to demonstrate the suitability of the underground reservoirs for CO2 storage based on their geological characteristics. The research addressed the potential of geological formations for fossil CO2 storage in the Baltic States to support the goal of achieving carbon neutrality in the region. The geological, technical, and economic feasibility for CO2 storage has been assessed in terms of carbon sequestration in geological structures and the legal framework for safe geological storage of fossil CO2. Results indicate that prospective structural traps in the Baltic States, with reasonable capacity for CO2 storage, occur only in Southwestern Latvia (onshore) and in the Baltic Sea (offshore), whilst other regions in the Baltics either do not meet basic geological requirements, or have no economically feasible capacity for CO2 storage. Based on the examination of geological characteristics, the most fitting is the middle Cambrian reservoir in the Baltic sedimentary basin, and one of the most prospective structural traps is the geological structure of Dobele, with an estimated storage capacity of 150 Mt CO2. This study revealed that the storage capacity of the middle Cambrian reservoir (up to 1000 Mt CO2) within the borders of Southwestern Latvia is sufficient for carbon capture and safe storage for the whole Baltic region, and that geological structures in Latvia have the capacity to store all fossil CO2 emissions produced by stationary sources in the Baltic States for several decades.